Value-ology : Aligning sales and marketing to shape and deliver profitable customer value propositions - Kelly, Simon; Johnston, Paul; Danheiser, Stacey (Springer International Publishing, 2017)
This book offers both marketing and sales professionals a rare combined insight into both worlds to continuously capture customer intelligence and create value, by blending detailed research with academic rigor and commercial experience of the authors in both Europe and North America. It has never been easier to produce great marketing content and sales collateral. And yet, 90% of the content that marketing produces is NEVER used by sales. Why not? Because it's not relevant to the audience or the prospect doesn't even know the content exists. Furthermore 58% of deals end up in "no decision" because Sales has not presented value effectively. Companies are creating lots of noise but failing to resonate with the customers. So what? The danger, aside from marketing wasting tens of millions of dollars on ineffective content and tools, is that customers will disengage. 94% of prospects say they have completely disengaged with vendors because of irrelevant content. In order to grow fast, the authors argue, Sales and Marketing teams need to slow down. They need to work together to truly understand their customers' needs, wants, motivations and pain points so that they can offer customized "value". The book sets out how to establish a formal program to continuously capture customer intelligence and insights -- the shiny gems of understanding that help prospects to connect the dots -- so that value can be consistently articulated in marketing and sales conversations. By integrating the best ideas and practice from commercial experience and academic research the authors show how to create value across the entire marketing and sales value chain -- not only get a new customer, but to continue to create value for future purchases by creating "post-sales" value.
Keywords: Marketing -- Management.; Strategic planning.; Customer relations.; Marketing research.; Customer services.; Success in business.; Market segmentation.; Sales personnel.; elektronické knihy; electronic books